(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
This work addresses how the research function is developed in the Law degree program of a public university in Argentina, focusing on the research scholarship program that the institution grants to students. It describes the regulatory framework that encourages this function, the conditions that arise in legal careers, who and what topics have been investigated during the last 10 years and updates the issue of mainstreaming the gender perspective in the curricularization of research. We conclude that, although there are some changes at the level of current regulations that have strengthened research and that the student body has a very good opinion about this activity, the research function still does not have much visibility nor is it usually chosen during the degree as a responsibility of the professional profile for future performance, nor have the actions aimed at its curricularization actively tended to mainstream the gender perspective.